Aplikasi Online Shopping Berbasi Website Pada Toko Enggal Waras Jember - Chendera, Antonio Minggono; Palit, Henry Novianus; Dewi, Lily Puspa (Jurnal Infra, 2015)
The rapid development of techonology nowadays causes increased competition in business world, one example of technology application in business is online shopping website, promoting goods via internet. The transaction progress in Enggal Waras store is still done manually, causing the transaction must be done inside the store (customer must come to the store to buy goods), moreover often happen the refusing of customer because the goods that the customer asked is not available in the store. To overcome this problem, then an online shopping website is designed for Enggal Waras store.This website is made using PHP as programming language, MySQL as database, and Apache as web server.From the system examination with questionnaire, website get the highest point 3,8 out of 5 for the easiness to operate. From that we can conclude that the websiteâs features are adequate for user needs and can be operated easily.Â